Note sur la tradition manuscrite d'un passage disputé du discours 38 de Grégoire de Nazianze (BHG 1938) - Macé, Caroline (Analecta Bollandiana, 2004)
In a small number of Greek MSS, Gregory of Nazianzus' 38th homily contains an addition of a few lines which does not belong to the original tradition of the text. This addition is edited here on the basis of 19 Greek MSS and two independent Syriac translations. The Greek MSS all belong to a well known textual family (family M according to Sinko's classification) and several of them were copied in Southern Italy. This case is an illustration of the existence of at least a cultural and well established link between the Near East and Southern Italy.